2021
DOI: 10.21608/cupsj.2021.77577.1021
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Tuberculosis is the Leading Presentation among Hospitalized Children: A Single-Center Experience in a Decade

Abstract: Background: With an incidence of twelve tuberculosis (TB) cases for every 100,000 persons in 2019, Egypt is considered a medium-burden country. Nevertheless, guidelines and studies for admission of pediatric TB cases are lacking in developing countries. Aim of the Work:To describe the clinical presentations of hospitalized pediatric TB cases. Materials and Methods: A retrospective analytical study of data collected from the inpatient medical files of children with confirmed TB, from the archives of Giza Chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Найпоширенішою клінічною формою ПТБ у досліджуваних дітей незалежно від віку був ТБ ПЛВ (40,4 %), тоді як за даними інших дослідників частка цієї клінічної форми становить від 26,2 до 40,6 % [4,12,14]. Однак за даними B. Santiago-Garcia та співавт.…”
Section: результати та обговоренняunclassified
See 1 more Smart Citation
“…Найпоширенішою клінічною формою ПТБ у досліджуваних дітей незалежно від віку був ТБ ПЛВ (40,4 %), тоді як за даними інших дослідників частка цієї клінічної форми становить від 26,2 до 40,6 % [4,12,14]. Однак за даними B. Santiago-Garcia та співавт.…”
Section: результати та обговоренняunclassified
“…C. Basanti та співавт. (2021) також установили, що ТБ з ураженням нервової системи частіше трапляється у дошкільному віці [4]. У нашому дослідженні виявлено схожу тенденцію: ТБ мозкових оболонок і ЦНС у дітей першого року життя діагностували статистично значущо частіше, ніж у наступних вікових групах (р 1 < 0,01; р 2 < 0,05), тоді як ТБ кісток і суглобів у них не траплявся на відміну від дітей віком 2-9 і 10-14 років.…”
Section: результати та обговоренняunclassified
“…Twenty-two percent had a history of TB in their family [15]. While in Egypt, it was found that the incidence rate of TB was 12 per 100,000 people, 6% of whom were children 14 years of age and younger [16]. Iraq adopted the DOTS strategy in April 1998, and 100% coverage was assumed to have been achieved in the early 2000s, which helped to reduce its incidence.…”
Section: Introductionmentioning
confidence: 99%

Prevalence of Tuberculosis in Children

Abdulsattar M.Al-Mashhadani ,,
Al-Majamie ,,
Abdulsattar M.Al Mashhadani ,
et al. 2024
djm